Prospects for the protection of religious pluralism (Poland, Hungary, Romania, Bulgaria) - Orlin, Theodore (Nordisk judaistik/Scandinavian Jewish Studies, 1992)
The drastic changes that have dramatically altered the political fabric of Europe raise significant questions as to the future of the interrelationship of religions with states whose political structure is now in flux. A commitment to pluralism, democracy, and respect for religious belief and practice is easily made. The difficult question is the manner in which it is going to be accomplished and secured. Further, given the often strong interaction between nationalistic goals and religious identity, the call for democracy and human rights were and often are in the mutual interest of the religious establishment and those who have nationalistic agendas. Once the immediate goal has been achieved, and religions are free to function, conceivably there is a potential that adherents of a majority religion can use their political dominance to obtain privileges at the expense of minority beliefs. This is especially true due to the long period of abuse perpetrated by states antagonistic to religion. It is not hard to comprehend a desire to return to the status quo and reimpose conditions that existed prior to the establishment of anti-religious regimes and recreate conditions favorable to a majority religion. This article considers the situation in Poland, Hungary, Romania and Bulgaria.